Metal- and photocatalyst-free, visible-light-initiated C3 a-aminomethylation of quinoxalin-2(1H)-ones via electron donor-acceptor complexes - More, Devidas A.; Shirsath, Sachin R.; Muthukrishnan, M. (Journal of Organic Chemistry, 2023)
We report a metal- and photocatalyst-free C3 a-aminomethylation of quinoxalin-2(1H)-ones with N-alkyl-N-methylanilines. The reaction proceeds through the formation of a photoactivated electron donor-acceptor complex between quinoxalin-2(1H)-ones and N-alkyl-N-methylanilines. The present method provides a mild and environmentally friendly protocol that exhibits good atom economy and excellent functional group tolerance to obtain a library of biologically significant C3 a-aminomethylated quinoxalin-2(1H)-ones in good yields.